IRAK-4 inhibition: emavusertib for the treatment of lymphoid and myeloid malignancies - Parrondo, Ricardo D.; Iqbal, Madiha; Von Roemeling, Reinhard; Von Roemeling, Christina; Tun, Han W. (Frontiers in Immunology, 2023)
Several studies have identified mutations in the MYD88L265P gene as a key driver mutation in several B-cell lymphomas. B-cell lymphomas that harbor the MYD88L265P mutation form a complex with phosphorylated Bruton’s tyrosine kinase (BTK) and are responsive to BTK inhibition. However, BTK inhibition in B-cell lymphomas rarely results in a complete response and most patients experience eventual disease relapse. Persistent survival signalling though downstream molecules such as interleukin 1 receptor-associated kinase 4 (IRAK-4), an integral part of the “myddosome” complex, has been shown to be constitutively active in B-cell lymphoma patients treated with BTK inhibitors. Emerging evidence is demonstrating the therapeutic benefit of IRAK-4 inhibition in B-cell lymphomas, along with possibly reversing BTK inhibitor resistance. While MYD88 gene mutations are not present in myeloid malignancies, downstream overexpression of the oncogenic long form of IRAK-4 has been found in acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS), particularly in AML and MDS that harbor mutations in splicing factors U2AF1 and SF3B1. These data suggest that the anti-leukemic activity of IRAK-4 inhibition can be exploited in relapsed/refractory (R/R) AML/MDS. In this review article, we discuss the currently available pre-clinical and clinical data of emavusertib, a selective, orally bioavailable IRAK-4 inhibitor in the treatment of R/R B-cell lymphomas and myeloid malignancies.